Chrysomya chani Kurahashi (Diptera: Calliphoridae), a blow fly species of forensic importance: morphological characters of the third larval instar and a case report from Thailand - Kabkaew L. Sukontason; Tanin Bhoopat; Anchalee Wannasan; Narin Sontigun; Sangob Sanit; Jens Amendt; Chutharat Samerjai; Kom Sukontason (Oxford University Press, 2018)
Blow flies are worldwide the most important insects from a forensic point of view. In Thailand, aside from the two most common species, Chrysomya megacephala (F.) and Chrysomya rufifacies (Macquart), Chrysomya chani Kurahashi was also found to be of forensic importance. We present a case of a human female cadaver in its bloated stage of decomposition, discovered at Pachangnoi Subdistrict, northern Thailand. Entomological sampling during the autopsy displayed an assemblage of numerous dipteran larvae. Macroscopic observations showed the coexistence of third instar larvae of the three blow flies C. megacephala, Chrysomya villeneuvi Patton, an unknown blow fly species and one muscid, Hydrotaea sp. The minimum post-mortem interval was estimated to be six days, based on the developmental rate of C. megacephala. The ID of the unknown larva, which is the focus of this report, was revealed later as C. chani by DNA sequencing, using a 1205 bp of cytochrome c oxidase subunit I (COI). The occurrence of C. chani on a human body revealed the need to analyse and describe the morphology of its immature stage, to enable forensic entomologists to identify this fly species in future cases. The morphological examination of the third instar was performed, revealing peculiar characteristics: protuberant tubercles encircling abdominal segments; 9-11 lobes on the anterior spiracle; six prominent pairs of tubercles along the peripheral rim of the eighth abdominal segment; a heavily sclerotized complete peritreme of the posterior spiracles. A key to differentiate the third instar of blow flies of forensic importance in Thailand is provided.